Numerical modelling of micron particle inhalation in a realistic nasal airway with pediatric adenoid hypertrophy: A virtual comparison between pre- and postoperative models - Qinyuan Sun; Jingliang Dong; Ya Zhang; Lin Tian; Jiyuan Tu (Frontiers Media S.A., 2023)
Adenoid hypertrophy (AH) is an obstructive condition due to enlarged adenoids, causing mouth breathing, nasal blockage, snoring and/or restless sleep. While reliable diagnostic techniques, such as lateral soft tissue x-ray imaging or flexible nasopharyngoscopy, have been widely adopted in general practice, the actual impact of airway obstruction on nasal airflow and inhalation exposure to drug aerosols remains largely unknown. In this study, the effects of adenoid hypertrophy on airflow and micron particle inhalation exposure characteristics were analysed by virtually comparing pre- and postoperative models based on a realistic 3-year-old nasal airway with AH. More specifically, detailed comparison focused on anatomical shape variations, overall airflow and olfactory ventilation, associated particle deposition in overall and local regions were conducted. Our results indicate that the enlarged adenoid tissue can significantly alter the airflow fields. By virtually removing the enlarged tissue and restoring the airway, peak velocity and wall shear stress were restored, and olfactory ventilation was considerably improved (with a 16∼63% improvement in terms of local ventilation speed). Furthermore, particle deposition results revealed that nasal airway with AH exhibits higher particle filtration tendency with densely packed deposition hot spots being observed along the floor region and enlarged adenoid tissue area. While for the postoperative model, the deposition curve was shifted to the right. The local deposition efficiency results demonstrated that more particles with larger inertia can be delivered to the targeted affected area following Adenoidectomy (Adenoid Removal). Research findings are expected to provide scientific evidence for adenoidectomy planning and aerosol therapy following Adenoidectomy, which can substantially improve present clinical treatment outcomes.